Wpływ wybranych elementów charakterystyki drzewostanów na intensywność występowania kornika drukarza Ips typographus (L.) w Beskidzie Żywieckim - Grodzki, Wojciech; Kosibowicz, Mieczysław; Starzyk, Jerzy (Leśne Prace Badawcze, 2014)
Recently, Norway spruce stands in Beskid Żywiecki (Western Carpathians) have been plagued by bark beetle outbreak affecting an extensive area over a large range of altitudes. Georeferenced data (2356 records) from 2009–2011 of the volume of felled spruces showing insect infestation in forest sub-compartments were analysed with respect to selected site and stand characteristics. The infestation intensity varied between individual parts of the examined area. Spruce mortality, recorded evenly across all slope expositions, was higher in the zones 800 m – 1000 m and above 1000 m than in the zone below 800 m. The infestation intensity increased slightly with spruce representation in the stands and was higher in stands older than 80 years. There was no clear correlation between spruce mortality and site quality. However, in areas with more diverse and fertile sites mortality was lower. In overall, the results obtained in this study are in line with previous knowledge on the subject, but patterns describing bark beetle preferences in infested areas appear to be less pronounced than those found in earlier publications. Risk assessment and current planning of forest protection measures in stands affected by bark beetle outbreaks should be based on the here described characteristics of spruce susceptibility to insect infection.